Blood parameters and enzymatic and oxidative activity in the liver of chickens fed with calcium anacardate - Cruz, Carlos Eduardo; Freitas, Ednardo; Braz, Nádia; Salles, Rosa Patrícia; Silva, Isaac Neto (Revista Ciência Agronômica, 2018)
The aim of this research was to evaluate the inclusion of calcium anacardate (CAC) as a source of anacardic acid in the diet of broiler chickens on blood parameters, and enzymatic and oxidative activity in the liver. A total of 840 male chicks, one day old, were kept in a completely randomised experimental design, with six treatments and seven replications of 20 birds, totalling 140 birds per treatment. The treatments consisted of feed without the addition of growth promoter (GP), feed with GP, and feed with no GP and the addition of CAC at levels of 0.25, 0.50, 0.75 and 1%. The biochemical blood variables to be analysed were uric acid, total cholesterol, HDL, LDL, creatinine, AST, ALT, triglycerides, total erythrocytes, haemoglobin, haematocrit, mean corpuscular volume, corpuscular haemoglobin concentration, total plasma protein, total leukocytes, heterophils, lymphocytes, platelets and heterophil/lymphocyte ratio. The concentrations of superoxide dismutase, glutathione peroxidase and malondialdehyde were analysed for the enzymatic and oxidative parameters in the liver. There were no significant differences between treatments in the blood parameters or the enzymatic and oxidative activity in the liver of the chickens, demonstrating that the use of calcium anacardate as a source of anacardic acid is non-toxic, and does not affect these parameters.